The classroom assessment scoring system as a measure of effective teaching to address the learning crisis. - Viticia,Thames (Metro Manila, Philippines Asian Development Bank, 2018)
Despite the remarkable progress in access to education, the learning crisis in South Asia continues to be a serious concern. To explore solutions, the Asian Development Bank organized a knowledge sharing workshop on improving education quality through supporting teaching activities and teacher assessment in Dhaka, Bangladesh, on 6 November 2017.The workshop focused on teacher professional development since teachers role is the most significant in school factor impacting student achievement. The workshop discussed how the Classroom Assessment Scoring System could be used to measure effective teacher student interactions through emotional support, classroom organization, and instructional support. Potential uses of CLASS include teacher professional development, monitoring, and evaluation.
Keywords: Computer-assisted instruction -- Study and teaching; Educational technology industries; Electronic books